How sequence variants of a plastid-replicating viroid with one single nucleotide change initiate disease in its natural host. Issue 7 (3rd July 2019) - Delgado, Sonia; Navarro, Beatriz; Serra, Pedro; Gentit, Pascal; Cambra, Miguel-Ángel; Chiumenti, Michela; De Stradis, Angelo; Di Serio, Francesco; Flores, Ricardo
ABSTRACT: Understanding how viruses and subviral agents initiate disease is central to plant pathology. Whether RNA silencing mediates the primary lesion triggered by viroids (small non-protein-coding RNAs), or just intermediate-late steps of a signaling cascade, remains unsolved. While most variants of the plastid-replicating peach latent mosaic viroid (PLMVd) are asymptomatic, some incite peach mosaics or albinism (peach calico, PC). We have previously shown that two 21-nt small RNAs (PLMVd-sRNAs) containing a 12–13-nt PC-associated insertion guide cleavage, via RNA silencing, of the mRNA encoding a heat-shock protein involved in chloroplast biogenesis. To gain evidence supporting that such event is the initial lesion, and more specifically, that different chloroses have different primary causes, here we focused on a PLMVd-induced peach yellow mosaic (PYM) expressed in leaf sectors interspersed with others green. First, sequencing PLMVd-cDNAs from both sectors and bioassays mapped the PYM determinant at one nucleotide, a notion further sustained by the phenotype incited by other natural and artificial PLMVd variants. And second, sRNA deep-sequencing and RNA ligase-mediated RACE identified one PLMVd-sRNA with the PYM-associated change that guides cleavage, as predicted by RNA silencing, of the mRNA encoding a thylakoid translocase subunit required for chloroplast development. RT-qPCR showed lower accumulation of this mRNA in PYM-expressing tissues. Remarkably, PLMVd-sRNAs triggering PYM and PC have 5ʹ-terminal Us, involving Argonaute 1 in what likely are the initial alterations eliciting distinct chloroses.